2018
DOI: 10.1002/ece3.3770
|View full text |Cite
|
Sign up to set email alerts
|

Ecological differentiation, speciation, and rarity: How do they match in Tephroseris longifolia agg. (Asteraceae)?

Abstract: Tephroseris longifolia agg. is a complex group of outcrossing perennials distributed throughout Central Europe. Recent morphological study revealed six morphotypes corresponding to five previously distinguished subspecies, together with Alpine and Pannonian morphotypes of T. longifolia subsp. longifolia. The delimited morphotypes differ in relative DNA content, geographical range, and rarity. We compared ecological niches of the six morphotypes in order to assess the impact of ecological differentiation on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Griseb. & Schenk [ 26 ], and Minuartia verna (L.) Hiern [ 8 ], albeit sometimes argued to be of minor evolutionary relevance [ 24 ] or suggested to be a result of an experimental artefact [ 27 ]. Nevertheless, this variation can be a result of microevolutionary differentiation and can reflect taxonomic heterogeneity [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Griseb. & Schenk [ 26 ], and Minuartia verna (L.) Hiern [ 8 ], albeit sometimes argued to be of minor evolutionary relevance [ 24 ] or suggested to be a result of an experimental artefact [ 27 ]. Nevertheless, this variation can be a result of microevolutionary differentiation and can reflect taxonomic heterogeneity [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown correlations between intraspecific variation of GS and morphological or environmental factors, as well as geographical distribution [ 5 , 26 , 30 , 31 , 32 , 33 , 34 , 35 ], but exact causes of this variation, and thus the interpretation of GS heterogeneity, remains a challenging task [ 35 , 36 , 37 ]. For instance, GS is a characteristic that may be related to the variation in plant phenology [ 38 ] and water availability [ 36 ], and may affect morphological characteristics such as seed size, nuclear and cell volumes, and duration of mitotic and meiotic cycles [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kelissa brasiliensis and H. pulchella also present narrower distributions than octoploid H. lahue. Even knowing that seed production alone cannot explain species endemism, rarity or restricted natural distribution (Münzbergová 2005;Powell et al 2011;Gabrielová et al 2013;Janišová et al 2018), rarer species often produce fewer seeds than their common relatives (Murray et al 2002;Lavergne et al 2004). Moreover, seed mass, which is expected to be inversely proportional to the number of seeds produced (Moles & Westoby 2004), was another almost fulfilled tradeoff premise, except for the octoploid H. lahue (i.e., with a large production of heavy seeds).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of polyploidy, GS can show a certain degree of variation within homoploid plant groups (Šmarda & Bureš, 2006; Loureiro et al, 2010; Frajman et al, 2015; Lazarević et al, 2015; Janišová et al, 2018), thus reflecting evolutionary dynamics not affected by genomic mutations (Pellicer et al, 2018). Neutral processes (Kang et al, 2014) and natural selection (Faizullah et al, 2021; Schley et al, 2022) can shape the amount of noncoding repetitive sequences in a genome, thus influencing GS variation (Macas et al, 2015; Hloušková et al, 2019).…”
Section: Introductionmentioning
confidence: 99%